1977
DOI: 10.1210/endo-100-3-619
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptors and Inhibition of Bone Cell Growth in Primary Culture12

Abstract: We have previously identified glucocorticoid binding proteins in cytosol of cells dispersed from fetal rat calvaria by collagenase digestion. The present study, employing primary culture of these cells, provides further evidence that these binding proteins represent glucocorticoid receptors. [3H]Dexamethasone bound to cytoplasmic extracts of cultured cells with an apparent Kdiss of 6.8 nM and exhibited approximately 8500 binding sites/cell. Nuclear translocation of [3H]dexamethasone was demonstrated with appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
1

Year Published

1979
1979
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(57 citation statements)
references
References 0 publications
4
51
1
1
Order By: Relevance
“…By contrast, interleukin-l/I up-regulates a,/&-integrin expression in MG-63 cells [24], resulting in cell growth inhibition of interleukin-l/I treated MG-63 cells [25]. Besides its effect on TSP expression, dexamethasone inhibits growth of human MG-63 osteoblastic cells (this study) as has been previously reported for cultured mouse osteoblastlike cells [8,9]. We have previously suggested that the growth-supportive effect of TSP could depend of a mechanism whereby cell surface-bound TSP stimulates secretion of prostaglandins which, in turn, allow cell proliferation to proceed [6].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…By contrast, interleukin-l/I up-regulates a,/&-integrin expression in MG-63 cells [24], resulting in cell growth inhibition of interleukin-l/I treated MG-63 cells [25]. Besides its effect on TSP expression, dexamethasone inhibits growth of human MG-63 osteoblastic cells (this study) as has been previously reported for cultured mouse osteoblastlike cells [8,9]. We have previously suggested that the growth-supportive effect of TSP could depend of a mechanism whereby cell surface-bound TSP stimulates secretion of prostaglandins which, in turn, allow cell proliferation to proceed [6].…”
Section: Discussionsupporting
confidence: 71%
“…Glucocorticoid-induced osteoporosis primarily involves decreased width of trabecular bone, suggesting reduction of trabecular osteoblast proliferation [7]. Osteoblastic cells have receptors for glucocorticoids [8], and cultured mouse MC3T3-El osteoblastic cells have been used to show that the glucocorticoid, dexamethasone, inhibits DNA synthesis and prostaglandin synthesis [9]. In addition, glucocorticoids also affect the expression of bone extracellular matrix proteins including type I collagen [lo], osteocalcin [11,12], alkaline phosphatase [12,13], osteopontin [14], bone sialoprotein [15], and fibronectin [ 161.…”
Section: Thrombospondinmentioning
confidence: 99%
“…Glucocorticoids have been shown to inhibit bone cell proliferation (43) and have a biphasic effect on type I collagen synthesis, a principal function of the osteoblast (16,44 -46). In addition to being dose-and treatment time-dependent, the effects of glucocorticoids also seem to depend on the stage of osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both stimulation and inhibition of cell proliferation by glucocorticoids have been reported in these organ cultures (Tenenbaum & Heersche 1985, McCulloch & Tenenbaum 1986, Kream et al 1997. In isolated osteoblast-like cell populations, glucocorticoids decrease cell proliferation but increase alkaline phosphatase activity (Chen et al 1977, Wong et al 1990, Cheng et al 1994. The effects of glucocorticoids on collagen expression in osteoblast-like cells, however, remain controversial.…”
Section: Introductionmentioning
confidence: 99%